Peran Modal Sosial Terhadap Keberlanjutan Industri Kerajinan Kecil di Indonesia: Penelitian - Khairani Alawiyah Matondang; Adel Syesaria Agustin Daole; Lidya Vanya F. Sihombing; Laurent Damai Yanti Silaban; William Barker Hutabarat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Small-scale craft industries make a significant contribution to the economy at both local and national levels, not only as a source of income but also as a means of preserving culture, regional identity, and creating employment opportunities. However, limitations in terms of capital, technology, and market access often become obstacles to their development. On the other hand, social capital, which includes networks of relationships, trust, norms, and values within craft communities, has proven to have a significant impact on business sustainability. This social capital can strengthen cooperation, reduce transaction costs, and improve the efficiency of interactions among industry actors. The sustainability of small-scale craft industries encompasses economic, social, and environmental aspects, which can be achieved through the optimal utilization of social capital. Nevertheless, challenges remain, such as weak solidarity, unhealthy competition, and low trust in formal institutions. This study examines the role of social capital in supporting the sustainability of small-scale craft industries and is expected to provide in-depth insights as well as strategic recommendations to strengthen social capital in order to create industries that are competitive, sustainable, and contribute to economic development and cultural preservation.